Achievement motivation among general diploma students in the light of some variables in the schools of Al Dakhiliyah Governorate - Sultanate of Oman - Al-Abri, Mohammed Nasser Ali (Journal of Educational and Psychological Sciences, 2022)
The aim of this study was to measure the level of motivation of achievement among students of the general diploma in the schools of AL Dakhiliyah Governorate in Sultanate of Oman in light of some variables (gender, birth order, and family income level). To achieve the aim of the study, the researcher used the descriptive correlative method and he used the measure of achievement motivation which consists of (36) paragraphs divided into five dimensions: (goal setting and its clarity, ambition, perseverance and perceived efficiency). It’s validity and steadfastness have been verified. A random sample was selected from the study population represented by the general diploma students in AL Dakhiliyah Governorate in Sultanate of Oman, 5452 male and female students enrolled in the academic year 2016-2017. The sample consisted of (825) male and female students i.e. (15%) of the size of the study population. The results of the study concluded in the following:- The level of achievement motivation was high in the study sample.- There were statistically significant differences at the level of significance (α≤0.05) in the estimations of the study sample on the level of achievement motivation attributed to gender variable in favor of females.- There were no statistically significant differences at the level of significance (0.05=α) in the estimations of the study sample on the level of achievement motivation attributed to the variable of birth order.- There were no statistically significant differences at the level of significance (0.05=α) in the estimations of the study sample on the level of motivation achievement attributed to the variable of family income level.The study came out with some recommendations, such as the need to pay attention to measuring and developing achievement motivation among school students in general and general diploma students in particular, in a developmental, preventive, and curative manner. In the field of research, this study recommended carrying out studies similar to the current study, but with more comprehensive and broader samples, as well as carrying out longitudinal studies to know the impact of collective counseling programs on the development of achievement motivation.
Keywords: Motivation of Achievement; Birth Order; General Diploma Students